360° video compression based on sphere‐rotated frame prediction. Issue 12 (10th September 2020) - Yu, Ning; Lin, Chunyu; Zhao, Yao; Liu, Meiqin; Zhang, Xue
Abstract : 360 ° video is very popular due to its 360 ° views of a scene. Although 360 ° videos are also compressed by a hybrid coding framework like 2D video, its high resolution and serious shape deformation affect coding efficiency. In equirectangular projection (ERP) format of 360 ° videos, if an object moves from equator regions to pole regions or vice versa, large deformation will be introduced and motion estimation cannot find the best‐matched part. To solve the above problem, the authors propose to generate a better reference frame for the current to be encoded frame. First, they project the frame prior to the current one from ERP to the sphere and rotate it at an appropriate angle depending on motion vectors. Subsequently, they insert this generated frame to the rear of the reference queue and let the encoder work as usual. The advantage is that the inserted frame has a more similar shape deformation as the current frame, which greatly helps motion estimation and makes full use of 360 ° video characters. Their method is simple and friendly compatible with the existing compression standard. Experiments prove that their method achieves 1.57% Bjøntegaard Delta (BD)‐gain compared with standard high efficiency video coding.